A ROD-LESS PISTON CORER FOR LAKE SEDIMENTS: AN IMPROVED, ROPE-OPERATED PERCUSSION CORER - Chambers J.W.; Cameron N.G. (My University, 2001)
A lightweight, percussion corer, suitable for use in remote lakes of moderate depth, is described. The operation of the corer and suggestions for securing and transporting long sediment cores are presented. In particular, the design and use of a recovery pot, which allows the retrieval of undisturbed cores from sediments of unknown depth, is detailed.